Long-lived triplet charge-separated state in naphthalenediimide based donor–acceptor systems. Issue 13 (26th February 2021) - Aster, Alexander; Rumble, Christopher; Bornhof, Anna-Bea; Huang, Hsin-Hua; Sakai, Naomi; Šolomek, Tomáš; Matile, Stefan; Vauthey, Eric
Abstract : Ultrafast electron transfer from singlet and triplet excited states in equilibrium results in the population of both singlet and triplet charge-separated states. Abstract : 1, 4, 5, 8-Naphthalenediimides (NDIs) are widely used motifs to design multichromophoric architectures due to their ease of functionalisation, their high oxidative power and the stability of their radical anion. The NDI building block can be incorporated in supramolecular systems by either core or imide functionalization. We report on the charge-transfer dynamics of a series of electron donor–acceptor dyads consisting of a NDI chromophore with one or two donors linked at the axial, imide position. Photo-population of the core-centred π–π* state is followed by ultrafast electron transfer from the electron donor to the NDI. Due to a solvent dependent singlet–triplet equilibrium inherent to the NDI core, both singlet and triplet charge-separated states are populated. We demonstrate that long-lived charge separation in the triplet state can be achieved by controlling the mutual orientation of the donor–acceptor sub-units. By extending this study to a supramolecular NDI-based cage, we also show that the triplet charge-separation yield can be increased by tuning the environment.